Alcohol-Related Risk of Driver Fatalities in Motor Vehicle Crashes: Comparing Data From 2007 and 2013–2014 - Romano, Eduardo (J Stud Alcohol Drugs, 2018)
OBJECTIVE: Using data from 2013–2014, this article aims to update alcohol-related fatal crash relative risk estimates, defined as the risk of dying in those crashes at different blood alcohol concentrations (BACs) relative to the risk of dying in a crash when sober (BAC = .00 g/dl), and to examine any change in risk that could have taken place between 2007 and 2013–2014. More specifically, we examine changes in risk among BAC = .00 g/dl drivers and among BAC > .00 g/dl drivers. METHOD: We matched and merged crash data from the Fatality Analysis Reporting System (FARS) and exposure data from the National Roadside Survey (NRS). To the matched database we applied logistic regression to estimate the changes in relative risk. RESULTS: We found that among sober (BAC = .00 g/dl) drivers, the risk of dying in a fatal crash decreased between 2007 and 2013–2014. For drinking drivers, however, no parallel reduction in the overall contribution of alcohol to the fatal crash risk occurred. Compared with 2007, in 2013–2014 the oldest group of drivers (age ≥ 35 years) were at an elevated crash risk when driving at low BACs (.00 g/dl < BAC < .02 g/dl). CONCLUSIONS: Although the decrease in crash risk for drivers with a BAC of .00 g/dl is encouraging, the consistency of the alcohol-related risk estimates over the last two decades suggests the need to substantially strengthen current efforts to abate drinking and driving.